America
1 online resource (8 volumes)
Keywords: The volumes in this set, originally published between 1967 and 2011, available as ebooks for the first time, include succinct, accessible books on two of the most important periods of American history which offer concise treatment of these major historical topics, as well as some lengthier, finest single-volume studies of the American Civil and Revolutionary Wars ever written and an outstanding reference tool in a 2 volume Encyclopedia. Among other things they: Bring central themes and problems into sharper focus. Discuss the pivotal roles played by Benjamin Franklin and Abraham Lincoln. Examine the role of medical doctors in the northern campaigns during the revolutionary war. Elucidate the character of the underlying moral and political problem of slavery. Discuss the social and political experience of the civil war whilst examining the centrality of what happened on the battlefield. Evaluate the legacy of the Civil War for America and for the world and emphasize its relationship to many of the dominating themes of modern history - democracy, freedom, equality and nationalism.